2012
DOI: 10.1007/s10792-012-9556-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tear osmolarity and ocular comfort between daily disposable contact lenses: hilafilcon B hydrogel versus narafilcon A silicone hydrogel

Abstract: The aim of this study was to evaluate tear osmolarity and ocular comfort with two different types of hydrogel daily disposable lenses. The right eyes of 15 first-time contact lens users were included in this prospective study. All eyes wore hilafilcon B silicone hydrogel contact lenses for 8 h (group 1). After 1 week without contact lenses, all eyes wore narafilcon A silicone hydrogel contact lenses for 8 h (group 2). Tear osmolarity measurement was performed before and after 4 and 8 h of each contact lens wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…These findings are in agreement with those of Sarac et al 34 who noted increased TFO in wearers of two different types of daily disposable lenses (hydrogel and silicone hydrogel) over short periods. Osmolarities were similar to our values when measured before CL insertion (293610.97 and 294613.66 mOsmol/L).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with those of Sarac et al 34 who noted increased TFO in wearers of two different types of daily disposable lenses (hydrogel and silicone hydrogel) over short periods. Osmolarities were similar to our values when measured before CL insertion (293610.97 and 294613.66 mOsmol/L).…”
Section: Discussionsupporting
confidence: 93%
“…It allows us to hypothesize that since the lenses were of the same material and transmissibility, the TF osmolarity assessment is proven to be an effective diagnostic tool for DED [16][17][18][40][41][42][43]. Tear osmolarity increases have been associated with CL wear in some studies [22,44,45], whereas other studies evidenced no changes [46,47]. According to Efron and colleagues, it is thought increased tear evaporation inducing electrolyte concentration changes could explain tear osmolarity build up associated with CL wear [21,48].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, [306][307][308][309][310] with one exception, 177 have found that contact lens wear results in increased osmolarity of the tear film or soft contact lenses, although there may not be an association with increased dry eye symptoms. 311 Either way, the sensory effect of tear film hyperosmolarity with contact lens wear may be difficult to measure because the soft contact lens is likely to represent a complex stimulus for the surface neural system. A hyperosmolar tear film that does not penetrate the contact lens is likely to stimulate only conjunctival neurons, which are relatively less sensitive to chemical stimuli compared with the cornea.…”
Section: Hyperosmolaritymentioning
confidence: 99%